Effects on the procurement process of pharmacies in Sweden in light of the COVID-19 pandemic - Feizi, Jawad; Johansson, Simon (My University, 2022)
The COVID-19 pandemic caused global disruptions and changed the business environment for health care services. Among health care services, the pharmaceutical industry covered a responsible role far larger than what it was accustomed to. When normal work procedures no longer were viable, the pharmacies were forced to change in order to supply medicine and other essentials. Specifically, the extreme increase in demand during a short period challenged the procurement of pharmaceutical goods. This forms the background to this master’s thesis. The purpose of this study is to investigate how the procurement process of pharmacies in Sweden has changed in the light of the pandemic both with regard to short- and long term changes. The theoretical frame of references is based on supply chain management, industrial purchasing, and literature on COVID-19. Additionally, a literature background of pharmaceutical supply chains and procurement was made to gain insight of how the pharmaceutical procurement process was designed. Based on the existing theory found along with the aim of the study, an analytical model was created to fit the overall purpose of the thesis. The method of the study is a multiple case study consisting of three pharmacies in Sweden. The cases have primarily been chosen to be of value from a supplier perspective and make up a diverse case pool to represent a wider part of the pharmacy market in Sweden. Representatives from each case company were interviewed in order to gain insights to their procurement processes and reactions to the pandemic. The data collected through interviews make up the majority of the empirical findings. The analysis showed that all case companies in the study applied both short- and long term changes to their procurement processes. To cope with the increased demand and volatility of certain pandemic related products, they changed their batch sizes and frequency of orders. The decision of increasing purchasing volumes was stressful for all the case companies. Though, they strengthened their resilience in different ways by creating crisis teams and overseeing their contingency plans. A trend of digitalisation was also discovered with more and more communication being made via online solutions. Furthermore, the pandemic forced both the pharmacies and their suppliers to increase their transparency and flexibility towards each other. This is not common in an otherwise closed business environment.
Keywords: Pharmaceutical supply chain, procurement process, COVID-19